The Effect of Service Quality on Loyalty Through Patient Satisfaction in Outpatient of Hospital X, Malang - Moh.Sholeh, - (Universitas Muhammadiyah Yogyakarta, 2021)
This study aimed at analyzing correlation between digital marketing and customer satisfaction and loyalty at general hospitals during the COVID-19 pandemic era. This study was a quantitative study with an observational design and a cross-sectional approach. The population of this study was the hospital’s customers with a total sample of 100 customers that had already received hospital services during the COVID-19 pandemic era and taken using a simple random sampling technique. Data analysis was done using Pearson’s correlation test. Digital marketing was perceived well by 84% of the respondents. Further, for customer satisfaction, it was shown that most respondents had a high satisfaction of 77%. For customer loyalty, it was shown that most respondents had a high loyalty of 75%. The result of data processing for correlation between digital marketing and the respondent’s satisfaction showed a significance level of 0.000 (p-value < 0.05) with an r-value of 0.827. Meanwhile, correlation between digital marketing and the respondent’s loyalty showed a significance level of 0.000 (p-value < 0.05) with an r-value of 0.655. Digital marketing and customer satisfaction and loyalty at general hospitals are correlated and it’s an effective way to improve hospital customer satisfaction and loyalty during the COVID-19 pandemic era.